A Workstation Environment for retrieving Text from Small to Large Unstructured Information Reservoirs - Clarke, James L.; Cooke , Jeffrey L. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
see PDF